2006
DOI: 10.1063/1.2185685
|View full text |Cite
|
Sign up to set email alerts
|

Richtmyer-Meshkov instability induced by shock-bubble interaction: Numerical and analytical studies with experimental validation

Abstract: International audienceThis paper deals with the numerical study of the interaction of a shock wave and a bubble. The three different density ratio cases between air and bubble are investigated: light/heavy, heavy/light and close density. The numerical simulations are compared to the experiments of Layes et al. Phys. Rev. Lett. 91, 17 2003. These three cases may allow us to better understand the vortex deposition by the baroclinic terms. Moreover, the behavior differences between the deformation of a bubble and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
59
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(62 citation statements)
references
References 31 publications
3
59
0
Order By: Relevance
“…The Richtmyer-Meshkov instability is generated by the interaction of the contact discontinuity (boundary of the heated channel) and the bow shock front which are under an angle with each other. So this situation is in accordance with the conditions of the Richtmyer-Meshkov instability initiation described in [10]. Fig.…”
Section: Richtmyer-meshkov Instability Generation and The Baroclinic supporting
confidence: 85%
“…The Richtmyer-Meshkov instability is generated by the interaction of the contact discontinuity (boundary of the heated channel) and the bow shock front which are under an angle with each other. So this situation is in accordance with the conditions of the Richtmyer-Meshkov instability initiation described in [10]. Fig.…”
Section: Richtmyer-meshkov Instability Generation and The Baroclinic supporting
confidence: 85%
“…5, flame initially moves towards right and becomes thin along with the time, the funnel grows linearly and arrives at right front of bubble before the occurrence of focusing (114 µs). At this point, the evolution of flame fronts is similar to that in inert case of references [22] and [23]. After shock focusing, left front of the distorted flame is slightly left-going, whereas the right front of the deformed flame continues to go towards right.…”
Section: Weak Shock Wave Casementioning
confidence: 64%
“…In addition, the developments of Freon-12 in air and helium environments were observed by Cowperthwaite and it was found that the flow density and velocity behind the shock coincide with the theoretical predictions [18]. Moreover, Giordano and Burtschell [19] concerned and compared the development of cylindrical and spherical heavy gas bubbles, and evaluated the change of bubble volume at later stage using a theoretical model. Recently, Raptor was adopted by Niederhaus et al for a parametric study in which several gases, such as helium, krypton and R12 were involved and several shock Mach numbers ranging from 1.1 to 5.0 were considered, and the interface compressibility ratio as well as the change of circulation was compared [20].…”
Section: Introductionmentioning
confidence: 79%